دور وسائط الاعلام الجديد في تنمية المستوى الثقافي لدى الطالب الجامعي - قاسم,أيمن; بلبي,وردة; مرغني,سمية (University of Eloued جامعة الوادي, 2024)
تيدؼ الد ا رسة إلى تحديد تأثير كسائط الإعلب عمى المستكل الثقافي لدل الطالب الجامعي، حيث ت التركيز في إشكالية الد ا رسة عمى مدل دكر كسائط الإعلب في تنمية المستكل الثقافي لدل الطالب الجامعي مف خلبؿ طمبة قس عمك الإعلب كالاتصاؿ بجامعة الكادم. كقد اعتمدنا في ىذه د ا رستنا عمى منيج المسح الاجتماعي مف خلبؿ أداتي الملبحظة كالاستبياف، حيث ت ذلؾ باستخدا أسمكب المسح الشامؿ عمى طمبة قس عمك الإعلب كالاتصاؿ بجامعة الكادم كالبالغ عددى 104 طالب. تكصمت الد ا رسة إلى مجمكعة مف النتائج كىي أف أغمب طمبة قس الاعلب كالاتصاؿ يتصفحكف كسائط التكاصؿ الاجتماعي باستخدا الياتؼ، كيستخدمكنيا مف 3 ساعات إلى 4 ساعات في اليك، كفي فت ا رت متفرقة في اليك، كيستخدمكنيا في البيت، كما أني يكافقكف عمى أف استخدامي لكسائط الإعلب لأنيا تقد لي خدمات عديدة. بالإضافة إلى أف أغمب طمبة قس الإعلب كالاتصاؿ يركف أف كسائط الإعلب تكفر لي معمكمات عف الجانب الصحي، كما أني يكافقكف عمى أف كسائط الإعلب تكفر لي ا زدا معرفيا حكؿ ما يتعمؽ بالجانب السياسي في بلبدى، كأصبحكا كاعيف بكؿ ما يخص الصحة بعد استخدامي لكسائط الإعلب، كأني يكافقكف عمى أف لكسائط الإعلب الجديد دكر مي في رفع كتنمية المستكل الثقافي لمطمبة الجامعييف.Abstract: The study aims to determine the impact of the media on the cultural level of the university student, where the focus in the problem of the study was on the extent of the role of the media in the development of the cultural level of the university student through the students of the Department of media and communication sciences at the University of the Valley. In this study, we relied on the Social Survey Methodology through the observation and questionnaire tools, as this was done using the comprehensive survey method on the 104 students of the media and communication sciences department at the University of the Valley. The study came to a set of results, namely that most students of the media and communication department browse social media using the phone, and use it from 3 to 4 hours a day, at sporadic intervals a day, and use it at home, and they also agree that their use of the media because it provides them with many services. In addition, most of the students of the media and communication department believe that the media provide them with information about the health aspect, and they also agree that the media provide them with increased knowledge about the political aspect in their country, and they became aware of everything related to health after using the media, and they agree that the new media has an important role in raising and developing the cultural level of university students.
Keywords: وسائط الإعلام; المستوى الثقافي،; role; Media; Development; cultural level; university student